2015
DOI: 10.1126/scitranslmed.3010525
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation increases mucin polymer cross-links to stiffen airway mucus gels

Abstract: Airway mucus in cystic fibrosis (CF) is highly elastic, but the mechanism behind this pathology is unclear. We hypothesized that the biophysical properties of CF mucus are altered because of neutrophilic oxidative stress. Using confocal imaging, rheology, and biochemical measures of inflammation and oxidation, we found that CF airway mucus gels have a molecular architecture characterized by a core of mucin covered by a web of DNA and a rheological profile characterized by high elasticity that can be normalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
198
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(210 citation statements)
references
References 41 publications
11
198
1
Order By: Relevance
“…They also had marked increases in sputum cell gene expression for type 2 cytokines, such as IL-5 and IL-13, and a relative increase in MUC5AC gene expression over MUC5B. This latter finding is relevant because cysteine domains are more prevalent in MUC5AC than in MUC5B (24), and we have previously shown that neutrophil-driven oxidation in the airways in cystic fibrosis can crosslink cysteine-rich mucin polymers to stiffen the mucus gel (11). In our studies, we found strong evidence that eosinophil-driven oxidation mediates mucus plug formation in asthma.…”
Section: Epo Generates Oxidants That Crosslink Cysteines and Stiffen mentioning
confidence: 75%
See 1 more Smart Citation
“…They also had marked increases in sputum cell gene expression for type 2 cytokines, such as IL-5 and IL-13, and a relative increase in MUC5AC gene expression over MUC5B. This latter finding is relevant because cysteine domains are more prevalent in MUC5AC than in MUC5B (24), and we have previously shown that neutrophil-driven oxidation in the airways in cystic fibrosis can crosslink cysteine-rich mucin polymers to stiffen the mucus gel (11). In our studies, we found strong evidence that eosinophil-driven oxidation mediates mucus plug formation in asthma.…”
Section: Epo Generates Oxidants That Crosslink Cysteines and Stiffen mentioning
confidence: 75%
“…Notably, the product of the reaction between thiocyanate and H 2 O 2 , catalyzed by EPO, is hypothiocyanous acid (HOSCN), which is known to target thiol groups as a cytotoxic mechanism (10). Recently, we have reported that oxidation of cysteine thiol groups -abundant in mucin polymers -is a mechanism of mucus gel stiffening in the lung (11), but the possibility that EPO promotes mucus plug formation by generating oxidants that modify mucins is not considered in reviews of the pathologic effects of eosinophils in the asthmatic airway (12).…”
mentioning
confidence: 99%
“…Third, we do not know if the marked increases in oxidized tyrosine that we detect in plasma occur in other inflammatory and/ or fibrotic lung disorders, such as cystic fibrosis or chronic obstructive pulmonary disease. Levels of o,o9-dityrosine and 3-nitrotyrosine have been shown to be elevated in sputum samples from adult patients with cystic fibrosis (37,38). Increased levels of 3-nitrotyrosine have been observed in exhaled breath condensate of patients with chronic obstructive pulmonary disease, and in bronchoalveolar lavage fluid from patients with acute respiratory distress syndrome (39,40).…”
Section: Discussionmentioning
confidence: 95%
“…The apparent discrepancy between these findings is likely attributable to the timing of evaluation of lung tissues after the final challenge with antigen, which differed. Of interest in this regard is the recent demonstration that airway mucins are targets for oxidation, manifested by disulfide-based cross-links that increase mucin elasticity in association with pathological mucus gel formation (28). It is not known at this time whether mucins are targets for PSSG, and whether this attenuates cross-linking.…”
Section: Discussionmentioning
confidence: 99%